Molecular evidence of Bartonella spp. in tropical wild birds from the Brazilian Pantanal, the largest wetland in South America - Alabí Córdova, Amir Salvador [UNESP]; Fecchio, Alan; Calchi, Ana Cláudia [UNESP]; Dias, Clara Morato [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (Springer Nature, 2024)
Despite the worldwide occurrence of bartonellae in a broad range of mammal species, in which they usually cause a long-lasting erythrocytic bacteremia, few studies reported Bartonella spp. in avian hosts. The present work aimed to investigate the occurrence and molecular identity of Bartonella spp. infecting birds in the Pantanal wetland, central-western Brazil using a multigene approach. For this purpose, blood samples were collected from 517 individuals from 13 avian orders in the states of Mato Grosso and Mato Groso do Sul. DNA was extracted from avian blood and 500/517 (96.7%) samples were positive in a conventional PCR targeting the avian β-actin gene. Nineteen (3.8%) out of 500 avian blood samples were positive in a qPCR assay for Bartonella spp. based on the nuoG gene. Among 19 avian blood DNA samples positive in the qPCR for Bartonella spp., 12 were also positive in the qPCR for Bartonella based on the 16S-23S RNA Intergenic region (ITS). In the PCR assays performed for molecular characterization, one 16S rRNA, three ribC, and one nuoG sequences were obtained. Based on BLASTn results, while 1 nuoG, 2 ribC, and 2 ITS sequences showed high identity to Bartonella henselae, one 16S rRNA and 2 ITS showed high similarity to Bartonella machadoae in the sampled birds. Bartonella spp. related to B. henselae and B. machadoae were detected, for the first time, in wild birds from the Brazilian Pantanal.
Keywords: Bartonella henselae; Bartonella machadoae; Bartonellosis; Birds